PENGARUH FEED RATE DAN DEPTH OF CUT TERHADAP KEKASARAN PERMUKAAN BAJA AISI 1045 CNC MILLING - Nugraha, Dwi Indra; Junaidi, Ahmad; ., Suparjo (Politeknik Negeri Sriwijaya, Indonesia, 2023)
This research is to determine the quality of machining products by testing the surface roughness. The research objective was to determine the effect of Feed Rate and Depth of Cut on the surface finish milling process on the surface roughness level. The method used in this research is the experimental method. The independent variables in this study were variations of Feed Rate and Depth of Cut where the Feed Rate values ​​taken was 300 mm/minute, 500 mm/minute, 700 mm/minute. The Depth of Cut values ​​taken was 0.1 mm, 0.2 mm, 0.3 mm and 0.4 mm. Based on the results of the roughness test of the Feed Rate and Depth of Cut variations of 0.1 mm each showed an average roughness value of 1.3005 μm, 1.70275 μm, 1.011 μm and 1.635 μm, the roughness test of the Feed Rate variation on Depth of Cut 0.2 mm each shows an average roughness value of 2.063 μm, 2.59325 μm, 2.31775 μm, and 2.75625 μm, roughness testing of the Feed Rate variation at a Depth of Cut of 0.3 mm shows average roughness values ​​of 3.01075 μm, 3.0215 μm, 3.01525 μm, and 3.091 μm, roughness testing of Feed Rate variation at Depth of Cut 0.4 mm each shows an average roughness value of 2.562 μm, 2.804 μm, 3.183 μm and 3.693 μm. Based on the standardization of the roughness value symbol according to (ISO) the results of research that has been done show that the value of the roughness number is N7-N8 in the range of 1.6 μm-3.2 μm.